2014
DOI: 10.1371/journal.pgen.1004597
|View full text |Cite
|
Sign up to set email alerts
|

Oligoasthenoteratozoospermia and Infertility in Mice Deficient for miR-34b/c and miR-449 Loci

Abstract: Male fertility requires the continuous production of high quality motile spermatozoa in abundance. Alterations in all three metrics cause oligoasthenoteratozoospermia, the leading cause of human sub/infertility. Post-mitotic spermatogenesis inclusive of several meiotic stages and spermiogenesis (terminal spermatozoa differentiation) are transcriptionally inert, indicating the potential importance for the post-transcriptional microRNA (miRNA) gene-silencing pathway therein. We found the expression of miRNA gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(117 citation statements)
references
References 48 publications
3
114
0
Order By: Relevance
“…miR-34b-5p is involved in the regulation of genes relevant for cell cycle control, apoptosis, and infertility 23, 24 . Thus, it could explain the increased cell death observed in the testes of mice exposed to the EDCs mixture.…”
Section: Resultsmentioning
confidence: 99%
“…miR-34b-5p is involved in the regulation of genes relevant for cell cycle control, apoptosis, and infertility 23, 24 . Thus, it could explain the increased cell death observed in the testes of mice exposed to the EDCs mixture.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, increased expression of these cell-cycle proteins in TKO mice represents a direct effect of their derepression upon miR-34/ 449 ablation. miRNAs of the miR-34/449 family were also reported to be involved in spermatogenesis (21,36,37). In particular, miR-34b/c and miR-449a/b/c are required for proper execution of meiosis in male gametes and during the maturation of spermatids (36).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs of the miR-34/449 family were also reported to be involved in spermatogenesis (21,36,37). In particular, miR-34b/c and miR-449a/b/c are required for proper execution of meiosis in male gametes and during the maturation of spermatids (36). It is likely that both the involvement of this miRNA family in spermatogenesis as well as their role in multicilia formation in the efferent ducts of the testes, described in our study, contribute to the infertility observed in male TKO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, miR-34c has also been shown to promote murine male germ cell apoptosis by targeting the transcription factor ATF1 in a p53-independent manner [122]. In mouse models, miR-34c and miR-34b were found to be highly expressed in post-mitotic male germ cells from primary spermatocytes up to round spermatids [121,123], and deletion of this locus along with miR-449 led to OAT and infertility [124]. Remarkably, miR-34c seems to extend its reproductive role into the zygote, as sperm-borne miR-34c has been shown to Patients with oligoospermia / oligoasthenozoospermia (80) and NOA (40) Spermatozoa and testicular tissues miR-429 was significantly increased, whereas miR-34b*, miR-34b, miR-34c-5p…”
Section: Spermatozoal Mirnas and Male Infertilitymentioning
confidence: 99%